Equivalence of Traditional and Internet-Delivered Testing of Word Fluency Tasks - Pesau, Heni Gerda; Luijtelaar, Gilles van (Faculty of Psychology, Diponegoro University, 2021)
Changes from traditional face-to-face to internet-delivered psychological assessment are urgently needed giventhe long-lasting pandemic, the general need for fast and efficient tests and test procedures, and easier availabilityand access for test-takers in remote settings. We used a quasi-experimental non-randomized group design for thecomparison of two word fluency test procedures: one traditional that is face-to-face (n = 30) and one supervisedvia internet (n = 30). Participants were 17-31 years, education level high school and Bachelor. The letters S, K, Twere used for the phonemic fluency test, for the emotion word fluency test subjects had to generate words relatedto subjective emotional feelings or the expression of emotions. The results showed that traditional administeredand internet-delivered testing are equivalent (our hypothesis) as seen from the absence of significant differencesbetween the two groups in the performances of all four word fluency tests (p > .05) and small effect sizes (Cohen’sd range < .5). Significant correlations were found between the fluency tasks, irrespective of the way of testadministration (p < .05). It can be concluded that the word fluency tasks can be assessed by supervised internet-delivered testing, but this is limited to a sample of young adults.